2014
DOI: 10.1123/jsr.2012-0130
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Injury by Limited and Asymmetrical Fundamental Movement Patterns in American Football Players

Abstract: The results of this study suggest that fundamental movement patterns and pattern asymmetry are identifiable risk factors for time-loss injury during the preseason in professional football players.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
136
3
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(159 citation statements)
references
References 36 publications
(50 reference statements)
7
136
3
4
Order By: Relevance
“…This research adds to the growing body of evidence for the predictive value of FMS component tests for injuries (5,21,23,25,30,32 # indicates sensitivity or specificity that is significantly different from FMS composite score. § indicates sensitivity or specificity that is significantly different from DS+ASLR score.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…This research adds to the growing body of evidence for the predictive value of FMS component tests for injuries (5,21,23,25,30,32 # indicates sensitivity or specificity that is significantly different from FMS composite score. § indicates sensitivity or specificity that is significantly different from DS+ASLR score.…”
mentioning
confidence: 89%
“…A recent review of FMS research indicated that there was "moderate scientific evidence" to support the use of FMS as a predictor of injury risk (27). Notably, for collision sport athletes, Kiesel et al (2007) showed that a FMS score ≤ 14 was predictive of serious injury (>21 days) in 4 professional American Football players (25), and that movement asymmetries highlighted by the FMS test increased relative injury risk (23). The link between low FMS scores and injury has also been demonstrated in female collegiate athletes (5), military (31,32) and general populations (30).…”
Section: Introductionmentioning
confidence: 99%
“…9 In addition, some investigators used the cut score of 14 because it was established in an earlier study. 6,7 For our study sample of NCAA Division II athletes, the cut score of 15 was the mean score, and it was the first score that established an sn higher than 50%.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 18 articles were included that investigated the link between FMS score and injury risk (Table 7) [17,19,27,[63][64][65][66][67][68][69][70][71][72][73][74][75][76][77]. Ten [19, 27, 64, 70-74, 76, 77] of the 18 studies reported an association between the FMS composite score and injury.…”
Section: Functional Movement Screenmentioning
confidence: 99%